Black Legends as a Political and Legal Instrument of the epoch of the Late Middle Ages and the Early Modern Period. The examples of Peter of Castile (1350-1369) and Philip II of Spain (1556-1598) (Estudios de Historia de España, 2019)
The socio-psychological and political-legal phenomenon of Black Legends is very interesting to study, at least because it is subtle and therefore, sometimes it is declared non-existent. However, this is a powerful and versatile political instrument. Applying an interdisciplinary approach, this phenomenon is studied to make clearer the process of creation of myths and a specific vision of the political world and its characters. As an example this research studies the figures of two Spanish kings who are the mostnotable characters in the political mythology, Pedro the Cruel or Peter of Castile (1350-1369) and Felipe II or Philip II of Spain (1556-1598).
Keywords: Black Legends; Political-Legal Mythology; Middle Ages; Modern Epoch; Pedro the Cruel; Felipe II